The diffusion effects in relativistic electron beam in an undulator - Ognivenko, V.V. (Вопросы атомной науки и техники, 2017)
We consider diffusion processes in momentum space of a relativistic electron beam moving in a spatially periodic magnetic field of an undulator. Basing on the dynamics of individual particles motion under the action of the pair interaction forces the longitudinal diffusion coefficient has been derived. The conditions for the high-gain self-amplification of spontaneous radiation in ultrashort-wavelength FELs have been discussed.